2022
DOI: 10.1038/s41598-022-16218-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IgM to phosphatidylcholine predict the response of multiple sclerosis patients to natalizumab or IFN-β

Abstract: We developed an ELISA assay demonstrating the high prevalence of serum IgM to phosphatidylcholine (IgM-PC) in the first stages of multiple sclerosis (MS). We aimed to analyze the role of serum IgM-PC as a biomarker of response to treatment. Paired serum samples from 95 MS patients were obtained before (b.t) and after (a.t) treatment with disease modifying therapies. Patients were classified as non-responders or responders to treatment, according to classical criteria. Serum IgM-PC concentration was analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…For that purpose, we evaluated morphology, velocity, and straightness of CD8 + T cells from four patients from each treatment response subgroup, upon interaction with VCAM-1 in an under-agarose setting to prevent nonspecific cell displacements. T cells tended to form homotopic aggregates upon natalizumab exposure (Figure 5G), as previously reported for other anti-VLA-4 antibodies 19,30 , but this phenomenon appeared to impact comparably T cells from both subgroups (Figure 5H). Analysis of cell area confirmed that T cells from non-responders tend to be resistant to the reduction of cell spreading evoked by natalizumab (Figure 5I).…”
Section: Cd8 + T Cells From Non-responder Patients Tend To Resist The...supporting
confidence: 83%
See 1 more Smart Citation
“…For that purpose, we evaluated morphology, velocity, and straightness of CD8 + T cells from four patients from each treatment response subgroup, upon interaction with VCAM-1 in an under-agarose setting to prevent nonspecific cell displacements. T cells tended to form homotopic aggregates upon natalizumab exposure (Figure 5G), as previously reported for other anti-VLA-4 antibodies 19,30 , but this phenomenon appeared to impact comparably T cells from both subgroups (Figure 5H). Analysis of cell area confirmed that T cells from non-responders tend to be resistant to the reduction of cell spreading evoked by natalizumab (Figure 5I).…”
Section: Cd8 + T Cells From Non-responder Patients Tend To Resist The...supporting
confidence: 83%
“…Currently, 30% of RRMS patients treated with natalizumab present evidence of disease activity 17 , not satisfactorily responding to the treatment according to the NEDA criteria. VLA-4 expression on Peripheral Blood Mononuclear Cells (PBMCs) 18 , serum levels of IgM specific for phosphatidylcholine 19 , metalloproteinases 20 , low percentage of CD5 + B cells 21 , age at prescription and disease duration 22 have been pointed as biological parameters related to natalizumab clinical response, although their robustness as predictive biomarkers remains to be established. To date, we therefore lack a pretreatment test to predict whether a given person with MS might benefit from the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that those with the highest levels of IgMPC responded subsequently to natalizumab. 78 This was expected because these patients have an aggressive course, with more relapses and faster increase of the disability, and they do not respond to first-line therapies. 78…”
Section: Antibodies To Lipids Predict the Response To Disease Modifyi...mentioning
confidence: 99%
“…In other words, the detection of IgMPC in serum samples is a diagnostic marker in this disease and has numerous advantages compared with the detection of OIgGBs. 73,78 It is an easily reproducible technique; it can be automatable, and it does not use CSF.…”
Section: Serum Antibodies To Pc Are a Diagnostic Marker In Msmentioning
confidence: 99%
See 1 more Smart Citation